Development of Students' Emotional and Spiritual Intelligence at MA Ahlussunnah Waljama'ah, East Ambunten Village - Fathul Rahman; Achmad Maulidi (STIT Attaqwa, 2025)
This study aims to examine the role of Aqidah Akhlak teachers in developing the emotional and spiritual intelligence of students at MA Ahlussunnah Waljama'ah, East Ambunten Village. Emotional and spiritual intelligence are two important aspects of education that contribute greatly to character building, behavior control, and the achievement of holistic educational goals. Aqidah Akhlak teachers have the responsibility not only as a material presenter, but also as a guide, motivator, and role model in instilling religious and moral values in students. This study uses a qualitative approach with a descriptive method, through the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that teachers play an active role in the learning process that is oriented towards the formation of emotional intelligence, such as the ability to recognize and manage the emotions of themselves and others, as well as spiritual intelligence, such as instilling the values of faith, patience, sincerity, and responsibility. This effort is carried out through a contextual learning approach, behavioral examples, and constructive interactions. Thus, Aqidah Akhlak teachers have a strategic role in shaping a generation that is not only intellectually intelligent, but also emotionally and spiritually mature.